2007
DOI: 10.1002/arch.20172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma‐irradiation on midgut proteolytic activity of the mediterranean fruit fly, Ceratitis capitata (Diptera: Tephritidae)

Abstract: The Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann), is a key pest of citrus in Spain because of significant yield losses and to quarantine restrictions. Biologically based control methods, such as the Sterile Insect Technique (SIT), which relies on the sterilization by irradiation of large numbers of insects, is gaining an increasing role in the control of medfly in Mediterranean areas. However, gamma-irradiation might damage the midgut epithelium cells, causing a lowering of nutritive assimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Few studies have attempted to define the physiological mechanisms underlying reduced response to food lures in these species, so it is difficult to speculate why γ -irradiation had no effect on response to cue-lure by Q-flies in our study. A recent study on Mediterranean fruit fly midgut proteolytic activity found no effect of sterilization (San Andres et al, 2007). The results from our study suggest that the ability of Q-flies to digest and absorb sources of nitrogen is unaffected by sterilization, leading to rates of sexual maturation (and attraction to cue-lure) similar to fertile (un-irradiated) flies.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Few studies have attempted to define the physiological mechanisms underlying reduced response to food lures in these species, so it is difficult to speculate why γ -irradiation had no effect on response to cue-lure by Q-flies in our study. A recent study on Mediterranean fruit fly midgut proteolytic activity found no effect of sterilization (San Andres et al, 2007). The results from our study suggest that the ability of Q-flies to digest and absorb sources of nitrogen is unaffected by sterilization, leading to rates of sexual maturation (and attraction to cue-lure) similar to fertile (un-irradiated) flies.…”
Section: Discussionsupporting
confidence: 43%
“…Sterile Q-flies used in SIT programmes are released as adults 24 -48 h after emergence (Meats et al, 2006). A recent study on Mediterranean fruit fly midgut proteolytic activity found no effect of sterilization (San Andres et al, 2007). This would improve estimates of sterile male abundance in the field derived from trap recaptures.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic and physiological abnormalities in sterile medflies and mexflies may be difficult to measure, and intricate studies are likely warranted. To this end, San Andres et al (2007) reported that radiation does not have an effect on digestive proteolytic activity in the medfly midgut, however, no regional analysis of the midgut was undertaken nor was the age of the medflies stated in that study. Stiles et al (1989) showed that radiation effects on the midgut of Glossina palpalis Vanderplank were indeed regional.…”
Section: Discussionmentioning
confidence: 96%
“…Symbiotic bacteria have been identified in the gut of several species of Tephritidae (Rubio & McFadden, ; Fitt & O'Brien, ; Lauzon et al., ; Kuzina et al., ; Marchini et al., ) and play a key role in protein absorption (Behar et al., ; San Andres et al., ). By adding symbionts to probiotic pre‐release diets, damage to the gut lining of irradiated medflies may have reverted and nutrient absorption capacity restored.…”
Section: Discussionmentioning
confidence: 99%